2007
DOI: 10.1007/s10903-007-9094-2
|View full text |Cite
|
Sign up to set email alerts
|

The Jade Ribbon Campaign: A Model Program for Community Outreach and Education to Prevent Liver Cancer in Asian Americans

Abstract: The Jade Ribbon Campaign (JRC) is a culturally targeted, community-based outreach program to promote the prevention, early detection, and management of chronic hepatitis B virus (HBV) infection and liver cancer among Asian Americans. In 2001, 476 Chinese American adults from the San Francisco Bay Area attended an HBV screening clinic and educational seminar. The prevalence of chronic HBV infection was 13%; only 8% of participants showed serologic evidence of protective antibody from prior vaccination. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 24 publications
1
59
1
Order By: Relevance
“…A 1 year follow-up study of a pilot hepatitis B screening effort of Chinese Americans in the area suggest that poor clinical follow-up for screened patients may be due to ineffective communication between patients and their providers, and the lack of awareness on the part of primary care providers about appropriate follow-up actions [34]. Together with our findings, these facts suggest that efforts to increase hepatitis B screening among Asians must both mobilize the public to request testing, as well as educate providers and institute processes that would remind them to test high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…A 1 year follow-up study of a pilot hepatitis B screening effort of Chinese Americans in the area suggest that poor clinical follow-up for screened patients may be due to ineffective communication between patients and their providers, and the lack of awareness on the part of primary care providers about appropriate follow-up actions [34]. Together with our findings, these facts suggest that efforts to increase hepatitis B screening among Asians must both mobilize the public to request testing, as well as educate providers and institute processes that would remind them to test high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly two-thirds of foreign-born HBV-infected Asian Americans are unaware of their infection status [9,30], 25-61% of Asian Americans remain susceptible to HBV infection [9,10,[31][32][33][34][35], and many other Asian Americans with HBV infection report having been vaccinated [36][37][38][39][40][41]. Screening identifies HBV carriers and allows for notification of uninfected family contacts and exposed sex partners for screening and vaccination [42].…”
Section: Importance Of Hbv Screening In Asian Americansmentioning
confidence: 99%
“…This program involves a strong collaboration between the public health system and organizations that provide educational outreach and links to medical care. A community-based campaign reported that 67% of patients diagnosed with CHB via a screening program had accessed medical care for HCC screening within 1 year after their diagnosis, and 78% had encouraged family-member screening for HBV [31]. The results demonstrate that targeted intervention is effective in reaching Asian Americans and not only increases HBV screening but also vaccination and access to, and utilization of, follow-up care [31,82].…”
Section: Hbv Screening Efforts In the Asian American Communitymentioning
confidence: 99%
“…8–10 Although the universal hepatitis B vaccination policies that were introduced in the region in the late 1980s have reduced the risk of contracting HBV, 11 a considerable proportion of Chinese Americans still have HBV infection. For instance, research showed that 21.4% of Chinese American participants in New York City had a chronic hepatitis B infection.…”
Section: Introductionmentioning
confidence: 99%